Relationship between unethical students and supportive education systems during online learning mode - Amir, Adibah; Ismail, Md Yusof (Kulliyyah of Engineering, 2021)
This paper examines the root causes behind the surging trend of students cheating during online teaching learning mode due to COVID-19 pandemic, a global issue that threatens the integrity of universities. It presents analysis on the defensive mechanism employed by universities by deploying an array of technologies to counter attack the cheating students. A number of key messages emerged from the analysis. This paper looks in detail at the core factor that led to this unethical phenomenon and discussed how these vary according to institutional mission, priorities and management style. The findings showed the vital role played by education champions and the significance of supportive top management were key factors for change. It is also recognized that responsibility for change must be shared between universities, ministry and accreditation bodies.